Does the Size of the Effect of Adverse Events at High Ages on Daily-Life Physical Functioning Depend on the Economic Conditions Around Birth? - Robert Scholte; Gerard J. van den Berg; Maarten Lindeboom; Dorly J. H. Deeg (Institute for the Study of Labor (IZA), 2014)
This paper considers determinants of physical-functional limitations in daily-life activities at high ages. Specifically, we quantify the extent to which the impact of adverse life events on this outcome is larger in case of exposure to adverse economic conditions early in life. Adverse life events include bereavement, severe illness in the family, and the onset of chronic diseases. We use a longitudinal data set of individuals born in the first decades of the 20th century. The business cycle around birth is used as an indicator of economic conditions early in life. We find that the extent to which functional limitations suffer from the onset of chronic diseases is larger if the individual was born in a recession. The long-run effect of economic conditions early in life on functional limitations at high ages runs primarily via this life event.
Keywords: I12; C33; J14; 330; functional limitations; long-run effects; business cycle; panel data; health; bereavement; chronic diseases